Association between MspI calpastatin gene polymorphisms, growth performance, and meat characteristics of Awassi sheep - JAWASREH, KHALEEL I; JADALLAH, ROLA; AL-AMAREEN, A H; ABDULLAH, ABDULLAH Y; AL-QAISI, ALAA; ALRAWASHDEH, IBRAHIM M; AL-ZGHOUL, MOH’’D BORHAN F; AHAMED, M KHAIR A; OBEIDAT, BELAL (The Indian Journal of Animal Sciences, 2017)
The association between the ovine calpastatin gene (CAST) genotypes, growth performance and meat characteristics of Awassi sheep was investigated. Homozygous (MM) and heterozygous (MN) genotypes of the CAST were obtained by RFLP, using Awassi ram lambs (age=7 to 14 days n= 80).A fattening trial was conductedusing 10 ram lambs MspI - of CAST genotypes (5 lambs from each genotype) (homozygous (MM) and heterozygous (MN). Lambs were weighed at the beginning of the experiment and the subsequent weights were measured biweekly before the morning feeding throughout the duration of the experiment. At the end of the fattening period, all lambs were slaughtered to evaluate carcass characteristics and meat quality. The results showed a significant association between CAST genotypes and growth rate and final body weight showing that lambs of the MN genotype had a higher average daily gain and final body weight compared to lambs of the MM genotype. The CAST gene genotypes showed a significant effect on some carcass components and meat quality parameters indicating that MN genotype showed lower total bone and higher meat to bone ratio than the MM genotype in the dissected leg cut. Furthermore, the MN genotype had a higher longissimus muscle weight compared to MM animals. Meat quality analysis showed that MN genotype lambs had higher shear force, lower cooking loss and lightness. It can be concluded that the CAST gene can be considered as one of the genes that control growth performance and meat quality traits.